Análise de acessibilidade nos prédios da Universidade Federal Rural do Semi-árido (UFERSA), localizado na cidade de Caraúbas - Costa Neto, Francisco Guedes da (Universidade Federal Rural do Semi-Árido, 2018)
The buildings are responsible for providing autonomy, independence and security, consequently generating comfort, through accessibility and independent of the conditions to which they are. Even with standards and legislation available in Brazil, public buildings, where there is a large influx of people, are inaccessible to people with special needs or who have reduced mobility. The objective of this study is to analyze accessibility conditions in the buildings of the Universidade Federal Rural do Semi-Árido (UFERSA), in the city of Caraúbas, in the light of NBR 9050/2015 and current legislation, as well as suggest changes in the environments of the institution. The results showed that the institution, although initially designed based on NBR 9050/2004, has some accesses and environments that are not in compliance with the current standard, requiring modification. It was concluded, therefore, that UFERSA, because it has people with special needs in the ambit of the institution, needs a readjustment of the public spaces that promote accessibility, social inclusion and a fiscalization policy regarding the execution of the engineering services, thinking always in the common good.
Monografia
Keywords: Universidade acessível; Edificações públicas; Readequação; ENGENHARIAS::ENGENHARIA CIVIL